The association of depressive symptoms with handgrip strength and gait speed in community-dwelling older adults: data from the baseline phase of Birjand Longitudinal Aging Study - Nazari, Tina; Moodi, Mitra; Fakhrzadeh, Hossein; Khodabakhshi, Huriye; Khorashadizadeh, Masoumeh; Arzaghi, Seyed Masoud; Shoaee, Shervan; Varmaghani, Mehdi; Ejtahed, Hanieh-Sadat; Sharifi, Farshad (BMC geriatrics, 2024)
Background Depression is a multifaceted condition with a high prevalence and burden to society. Handgrip strength (HGS) and gait speed (GS) are indices of physical health, which is linked to mental health. Previous studies have shown heterogeneity among countries in the association of physical parameters and depression. In this study, we aimed to investigate the association of HGS and GS with depressive symptoms in older adults. Methods This is a cross-sectional study analyzing data from the Birjand Longitudinal Aging Study, a cohort of community-dwelling older adults (≥ 60 years old). Depressive symptoms were assessed by the nine-item Patient Health Questionnaire. HGS was measured with a hand dynamometer in a sitting position, and GS was estimated by a 15-foot walk test at usual pace. Results Compared to participants in the first quartile, those in the second quartile of HGS had significantly lower odds of suffering from depressive symptoms, while GS was not significantly associated with depressive symptoms. A higher HGS was associated with a lower risk of moderate depressive symptoms, while a higher GS was related to a lower risk of moderately severe and severe symptoms. Conclusions Our findings suggest that older people residing in Birjand, Iran with a moderate HGS are less likely to suffer from depressive symptoms than those with lower HGS.